Critical lure source details are “correctly” attributed to both directly related and mediated lists - Alexa E. Tringali; Mark J. Huff (Frontiers in Psychology, 2025)
Studying lists of associatively related words often produces false recognition of non-studied critical lures (CL). This false memory illusion can be found both when word lists are directly related to a CL as in the DRM paradigm (e.g., water, bridge, run, for the CL river), and when words are indirectly related to CLs via non-presented mediators (e.g., faucet[water], London[bridge], jog[run], for the CL river). Mediated false memory is strong evidence for activation-monitoring processes over gist extraction as mediated lists lack a consistent gist theme. In the present study, we evaluated whether context details (font color) of studied lists are attributed to CLs when they are falsely recognized. Participants studied directly related and mediated word lists presented in one of two font colors, followed by a source test which required specification of the font color for recognized test items. When CLs were falsely recognized, participants were able to correctly identify the font color of the CL’s origin list for both list types at a higher rate than incorrect identification. Because mediated false recognition reflects implicit activation, this pattern indicates activation processes may include both semantic and perceptual source details.